Competition for control over the labour process as a driver of relocation of activities to a shared services centre. (June 2018) - Mezihorak, Petr
New approaches to studying multinational corporations sensitive to issues of power and politics often neglect the way power and politics in corporations shape workplaces, specifically labour processes and modes of their control. The article presents a case study of a firm's relocation of activities to a shared services centre. The relationships among the shared services centre, its client departments and the headquarters involve an ongoing combination of cooperation and competition, resulting in increased managerial control over labour processes and changes in corporate governance. The shared services centre established as a support unit aims to strengthen its position in the organizational structure by gaining control over labour processes and their modification. Competition with client departments for control over labour processes leads to the introduction of controlling mechanisms, norms and standards both in the centre and in client departments. These rules, on the one hand, limit uncertainty; on the other hand, they drive the fragmentation of labour processes, rendering them more codifiable and less complex. These effects make labour processes easier to control and, eventually, to relocate, which is advantageous for the headquarters. Changes in labour processes thus shape the relationships within the corporation and the space for power struggles and politics.